Age-related processing strategies and go–nogo effects in task-switching: an ERP study - Gaál, Zsófia A.; Czigler, István (Frontiers in Human Neuroscience, 2015)
We studied cognitive and age-related changes in three task-switching (TS) paradigms: 1) informatively cued TS with go stimuli, 2) informatively cued TS with go and nogo stimuli, 3) non-informatively cued TS with go and nogo stimuli. This design allowed a direct comparison, how informative and non-informative cues influenced preparatory processes, and how nogo stimuli changed the context of the paradigm and cognitive processing in different aging groups. Beside the behavioral measures (reaction time, error rate), event-related potentials (ERP) were registered to the cue and target stimuli in young (N=39, mean age= 21.6±1.6 years) and older (N=40, mean age=65.7±3.2 years) adults. The results provide evidence for declining performance in the older group: they had slower reaction time (RT), less hits, more erroneous responses, higher mixing costs and decreased amplitude of ERP components than the participants of the younger group. In the task without the nogo stimuli young adults kept the previous task-set active that could be seen in shorter reaction time and larger amplitude of cue-locked late positivity (P3b) in task repeat (TR) trials compared to task switch trials. If both go and nogo stimuli were presented, similar RTs and P3b amplitudes appeared in the TR and TS trials. In the complex task situations older adults did not evolve an appropriate task representation and task preparation, as indicated by the lack of cue-locked P3b, CNV, and target-locked P3b. We conclude that young participants developed explicit representation of task structures, but the presence of nogo stimuli had marked effects on such representation. On the other hand, older people used only implicit control strategy to solve the task, hence the basic difference between the age groups was their strategy of task execution.